What Works in School? Expert and Novice Teachers’ Beliefs about School Effectiveness - Fleckenstein, Johanna; Zimmermann, Friederike; Köller, Olaf; Möller, Jens (Frontline Learning Research, 2015)
In 2009, John Hattie first published his extensive metasynthesis concerning determinants of student achievement. It provides an answer to the question: “What works in school?” The present study examines how this question is answered by pre- and in-service teachers, how their beliefs correspond to the current state of research and whether they differ according to the teachers' level of expertise. Thus, it takes on a novel approach as it draws on data from two sources in the field of education -- empirical research and teachers’ beliefs -- and examines their similarities and differences. The teachers’ beliefs were elicited by asking N = 729 participants to estimate the effect sizes of several determinants of student achievement. Those were compared to the empirical effect sizes found by Hattie (2009). Profile correlations showed that expert teachers’ beliefs are more congruent with current research findings than those of novice teachers. We further examined where expert and novice teachers’ beliefs differ substantially from each other by using confirmatory factor analysis (CFA) and comparing group means in latent variables. Our findings suggest that teachers’ beliefs about school effectiveness are related to professional experience: Expert teachers showed a stronger overall congruence with empirical evidence, scoring higher in achievement-related variables and lower in variables concerning surface- and infrastructural conditions of schooling as well as student-internal factors. Results are discussed with regard to teacher-education practices that emphasize research findings and challenge existing beliefs of (prospective) teachers.